Posterior hemivertebra resection and reconstruction for the correction of old AO type B2.3 thoracic fracture kyphosis: A case report - Meng, Fanchao; Zhang, Xun; Chen, Tiantian; Li, Zhao; Fang, Yushi; Zhao, Wei; Xu, Jiaxing (Frontiers in Surgery, 2022)
Abstract. Background: Post-traumatic malunion is one of the main causes of kyphosis and usually has serious consequences. We report a case of kyphosis caused by an old AO type B2.3 thoracic fracture, which was corrected with posterior hemivertebra resection and reconstruction. Case presentation: A 41-year-old male was diagnosed with kyphosis caused by an old AO type B2.3 thoracic fracture. Preoperative examination and preparation were performed. His exam images showed a comminuted fracture in the left half of the T12 vertebral body, while chance-type fractures were seen in the right half of T12 vertebral body and its accessories. During the operation, posterior hemivertebra resection and reconstruction techniques were used to remove nearly half of the left vertebral body of the affected vertebra, preserve the right vertebral body and the facet joints of the affected vertebra, correct the kyphosis, and rebuild spinal stability. The patient's low back pain was completely relieved, and his thoracic kyphosis was corrected at the seventh post-operative day. CT reconstruction of the spine showed that the residual vertebrae healed well during his nine- and 18-month follow-ups. Continuous callus formation was observed inside and outside of the titanium cage at the reconstructed site, and there was no sign of subsidence of the titanium cage. The heights between the vertebrae were restored to within normal ranges and the physiological curvature of the thoracolumbar spine was achieved. The patient recovered well. Conclusion: This operation preserved the hemivertebral body and facet joints, and maintains intervertebral height and local stability, thus avoiding titanium cage collapse, titanium cage movement, and other complications. This surgical approach is ideal for treating complex thoracic vertebral kyphosis caused by old fractures, and is worth utilizing in the clinic.